Blue-Green Infrastructure in the Urban Heart: Detention Tanks for Flood Mitigation on Abdias de Carvalho Avenue in Recife-PE - Nóbrega, Lucas Emanuel de Oliveira; Moura , Micaella Raíssa Falcão de; Oliveira, Pedro Eugênio Silva de (Technical and Scientific Journal Green Cities, 2025)
Objective –To analyze the technical, environmental, and urban feasibility of installing rainwater retention tanks at the Hipódromo Jockey Club in Recife, PE, aiming to mitigate recurring flooding episodes on Avenida Engenheiro Abdias de Carvalho, an important thoroughfare in the city, through an integrated approach of blue-green infrastructure and Nature-Based Solutions (NbS).Methodology – The study adopted an applied, exploratory, and descriptive approach, based on a literature review, documentary analysis of hydrometeorological and urban data, the use of geotechnologies (ArcGIS, ESIG) for mapping and diagnosing the area, and field inspections for diagnosis and suggestions for retrofitting the existing drainage infrastructure.Originality/Relevance –The work contributes to the context of enlarging integrated sustainable urban drainage solutions in Brazilian coastal cities, helping to fill gaps in the use of large, underutilized urban areas as multifunctional blue infrastructure elements, also highlighting the academic and practical relevance of NbS strategies for climate adaptation.Results – The availability of approximately 105,000 m² of viable technical space was verified at the racetrack, with the potential to store significant volumes of rainwater. The analysis demonstrated the feasibility of integrating it with the existing gravity and penstock drainage system, demonstrating the potential technical effectiveness of the proposal in reducing peak flows and mitigating flooding on the avenue.Theoretical/Methodological Contributions –The study reinforces the applicability of NBS as an urban planning guideline, demonstrates the use of geotechnologies for hydrological diagnostics in urbanized areas, and proposes a blue infrastructure intervention model for densely sealed cities.Social and Environmental Contributions – The proposed solution contributes to reducing the socioeconomic impacts of flooding, improves road safety and urban mobility, prevents expropriations and the removal of native vegetation, preserves the landscape, and promotes greater city resilience to extreme hydrological events, aligning with the Sustainable Development Goals (especially SDG 6 - Clean Water and Sanitation and SDG 11 - Sustainable Cities and Communities).
Keywords: Urban drainage; Sustainability; Blue-Green infrastructure (BGI)